Expresión de antígenos de Babesia bovis y Cryptosporidium parvum en el ciliado Tetrahymena thermophila para el desarrollo de vacunas a subunidades - Montes, María Guadalupe (2022)
Tetrahymena thermophila is a free-living protozoon that has been used as a biotechnological platform for the expression of several recombinant antigens. In the present study, its ability to express vaccine candidates of Babesia bovis and Cryptosporidium parvum was evaluated. Both parasites are pathogenic apicomplexan protozoans responsible for a considerable morbidity and mortality of bovines. The glycosylphosphatidylinositol (GPI)-anchored antigens (GPI4) of B. bovis and GP60 of C. parvum were expressed in clones of T. thermophila, after transformation with corresponding recombinant episomal vectors. GPI functions as protein anchor and is a potent modulator of the host immune response. The ciliate was able to express GPI4 and GP60 in the parasite membrane. The optimized culture conditions for the expression of the recombinant antigens were determined at 5 ?g/mL Cl2Cd, a volume of 15 mL and a time of induction between 6 to 8 h. Based on these conditions, a culture of 1L in a bioreactor was successfully achieved. Finally, recombinant GP60 expressed by T. thermophila clones was recognized by sera from calves naturally infected with C. parvum demonstrating its immunoreactivity and the principal aptitude of the ciliate for recombinant expression of vaccine candidates.